A Growth and Phosphorus Uptake of Soybean (Glycine Max L.) in Response to Arbuscular Mycorrhizal Fungus Rhizophagus Intraradices Inoculation in Heavy Metal-contaminated Soils. Issue 6 (18th August 2021) - Adeyemi, Nurudeen Olatunbosun; Atayese, Mufutau Olaoye; Sakariyawo, Olalekan Suleiman; Azeez, Jamiu Oladipupo; Olubode, Adebanke; Ridwan, Mudathir; Adebayo, Rukayat; Adeoye, Samuel
ABSTRACT: The present study investigated the effect of arbuscular mycorrhizal fungus (AMF) Rhizophagus intraradices on plant growth and phosphorus (P) uptake of soybean ( Glycine max L.) in soils contaminated with different concentrations of heavy metals [copper (100 and 300 mg kg −1 ), lead (100 and 300 mg kg −1 ) and zinc (300 and 600 mg kg −1 )] and combination (Cu100 + Pb100 + Zn300) in a pot experiment. The bioaccumulation characteristics of the heavy metals in the plant tissues in terms of bioabsorption coefficient (BAC), bioconcentration factor (BCF) and translocation factor (TF) were also evaluated. The results showed R. intraradices inoculation significantly ( p < .01) enhanced soybean growth, P uptake and grain yield in all polluted soils compared to non-inoculated treatment. In addition, R. intraradices retained most of the heavy metals in the roots, with lesser translocation to the shoots and seeds. Exposure to 600 mg Zn kg −1 soil remarkably reduced the plant growth, P content and seed yield of the soybean. Copper uptake in the shoot was significantly increased in multi-metal contaminated soil with reduced lead and zinc compared to single polluted soils. This work suggests that Rhizophagus intraradices inoculation may be a potential and effective of AMF isolate for enhancing plant growth, P nutrition and stress tolerance in heavy metal-contaminated soil